Algorithm and architecture of data compression for wireless sensor node - Nor Alina Khairi (School of Microelectronic Engineering, Universiti Malaysia Perlis, 2015)
The objectives of the research are stated as below to model the Huffman algorithm using C language and Verilog Hardware Description Language (Verilog HDL); to evaluate the Huffman compression ratio's efficiency towards various wireless sensor node data; to design and analyse the Huffman circuit architecture's performance in terms of speed, power and energy consumption.